Development of an indexed score to identify the most suitable biological material to assess SARS-CoV-2 - Almeida-Silva, Marina (2024)
Introduction: The rapidly contagious process of respiratory viruses such as SARS-CoV-2 makes it urgent to multiply testing for diagnostics to identify the active viral shedding cases (current infection, carriage state, or, residual viral RNA) and decrease the risk of transmission to other patients and healthcare professionals. Although nasopharyngeal swabs (NPSs) are the most common specimen type used for COVID-19 diagnosis, they require supervision by a professional, and concerns have been raised regarding healthcare personnel exposure, difficulty in collection, and patient discomfort. Viral RNA can also be detected in specimens such as saliva, blood, bronchoalveolar lavage fluid, sputum, faeces, and urine. This study aimed to provide updated information about the most suitable biological material to diagnose SARS-CoV-2, considering the risk assessment, specialization needed, test cost, complexity of the collection, and sample treatment associated with the different types of specimens. Methods: An extensive search of scientific review articles were made to collect information about the biological specimens to identify SARS-CoV-2 in the urine, sputum, nasopharyngeal, oropharyngeal, bronchoalveolar (BAL), saliva, faeces, and blood. For this purpose, an index score was developed based on seven categories: Materials and Equipment; Infection Risk for the Health Professional; Infection Risk for the Patient; Collection; Cost; Specialized HR; and RNA Extraction Type. Results and Discussion: Each criterion from the index score was quoted from 1.0 to 5.0, and a sum was made to classify which specimen is the best choice to diagnose SARS-CoV-2, according to the chosen parameters. Data indicated that urine specimens are the most elementary biological sample to access. Regarding RNA extraction, NPSs, OPS, and BAL presented the maximum score. However, BAL has the lowest score regarding associated costs. Concerning sputum and saliva, all the aspects were evaluated with a score of 5.0 except for the RNA Extraction Type in sputum. Regarding the total scores of the multiple specimens, the lowest corresponds to BAL with a score of 1.7, followed by blood with 3.1 and NPSs and OPS with 3.6 and 3.7, respectively. Urine and faeces have the same value, 4.4, sputum has 4.9, and the highest and maximum possible value corresponds to saliva with 5.0, making this last specimen the most suitable for all considered parameters. Conclusion: Although OPS and NPSs are the most used specimens, there are better alternatives. Among all the specimens of the respiratory system, saliva is the most cost-effective specimen for performing SARS-CoV-2 diagnosis. Even though these infections are usually diagnosed clinically based on symptoms and local epidemiology, identification of the specific pathogen may affect clinical management and be crucial for containing potential outbreaks.